Pengaruh Diskon dan Kepercayaan Konsumen Terhadap Keputusan Pembelian Pada Pengguna Aplikasi Blibli - Pribadi, Firman Syakri; Rahmadhani, Yozi Sri (Pustaka Galeri Mandiri, 2025)
This study aims to determine the effect of discounts and consumer trust on purchasing decisions of users of the blibli application on students of the economics faculty of the University of West Sumatra. This research uses quantitative research with descriptive research methods. The sample in this study were students majoring in management at the economics faculty of the University of West Sumatra, using a purposive sampling method. Data were collected by distributing questionnaires that met the requirements of 33 people. The data analysis technique in this study used descriptive statistical analysis methods; test data quality using validity test, reliability test; classical assumption test using normality test, multicollinearity test, heteroscedasticity test; multiple linear regression analysis; hypothesis testing using t test, f test; and determinant coefficient analysis (R2). The results of multiple linear regression test Y = 15,803 + 0.021X1 + 0.677X2, and the T and F tests show that the discount does not have a significant effect on purchasing decisions on sig 0.927 > 0.05, consumer confidence has a significant effect on purchasing decisions on sig 0.002 < 0.05 and simultaneously discounts and consumer confidence have a significant effect on purchasing decisions on sig 0.000 < 0.05. while the Adjusted R Square value of 0.395 shows that 39.5% of the variation in purchasing decisions at blibli can be explained by the two independent variables, the remaining 59.5% is explained by other factors outside the study.